Knowledge, Attitude and Practice (KAP) towards Salt Intake and its Relationship with Blood Pressure (Jalalabad Medical Journal, 2025)
Hypertension is an important modifiable risk factor for cardiovascular disease. Excess salt intake is an etiological factor for hypertension. This study was designed to assess knowledge, attitude, and practice towards salt intake and its relationship with blood pressure. This cross-sectional study was conducted in Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, between September 1, 2022, and September 30, 2022, among patients attending out-patient departments of surgery, medicine, obstetrics, and gynaecology. A total of 214 respondents were included in the research following the purposive sampling technique. Out of 214 respondents, 36.9% added salt to their food before eating, and the majority (81%) of the respondents always added salt while preparing their food. Among all the respondents, 61.2% seem to consume the right amount of salt per meal, and 45.3% of them knew that too much salt intake can cause hypertension. Only 31.3% of respondents said it was very important to lower salt intake in their diet. The majority (93%) of respondents did not know the national recommendation for daily salt intake for adults. The relationship between knowledge about national recommendations for salt intake and the practice of avoiding table salt was found statistically not significant. There was no significant relationship between the knowledge of respondents about the occurrence of hypertension due to too much salt consumption and their practice of consuming table salt. Even though most respondents believe that they are eating the recommended amount of salt, the study reveals that the majority are unaware of the national recommendation of daily salt intake.Jalalabad Med J 2024; 21 (2); 41-46